Advances in Comprehensive Two-Dimensional Gas Chromatography (GC X GC) - Eiserbeck, Christiane; Nelson, R.; Reddy, C.; Grice, Kliti (The Royal Society of Chemistry, 2014)
Thirty years ago Giddings (1984) proposed a vision of 2D separation techniques that has only now been realised with comprehensive 2D gas chromatography (GC×GC). This technique has revolutionised the separation power of complex organic mixtures using chromatographic techniques. The additional dimension of separation compared to traditional 1D GC is particularly valuable for analyses of geological samples such as petroleum and rock extracts. Many applications have been explored in the past decade including monitoring of oil spills, tracking of contaminants, fingerprinting of crude oils, and detailed biomarker identification. Recent developments and applications across the geosciences are discussed and the potential of GC×GC unveiled.